The Kembar Manten in Java Majapahit Wedding Traditions in Mojokerto: Perspectives on Natural Law and Anthropology of Islamic Law - Hidayah, Khoirul; Syarifah, Umaiyatus; Muhammad, Muhammad; Bachri, Syabbul; Roibin, Roibin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Majapahit Java has customary law, namely rules prohibiting "kembar manten" marriages, namely two bride and groom couples marrying at the same time, and the walimah party is held together with the symbol 'kuwade' in one 'terop'. This study employs empirical legal methodologies, incorporating a phenomenological and anthropological approach. Meanwhile, the analytical tools encompass notions related to natural law, justice, and the anthropology of Islamic law. The collection of primary data was conducted through interviews of traditional authorities, religious leaders, knowledgeable individuals in the customary laws, and marriage practitioners who perform 'Kembar Manten' marriages in Mojokerto. The examination was conducted utilizing Thomas Aquinas' theory of natural law and justice, joining with the anthropology of Islamic law. In order to achieve justice in the natural law, it is necessary to have a policy and proportionality when making the walimah ursy, which is specifically created for a single wedding pair. In the field of the Islamic law anthropology, the 'Kembar Manten' refer to customs and customary laws that are regarded obligatory and advantageous. They are intended to promote the welfare of both the bride and groom's families. Neither the Qur’an nor the Hadith provide any instructions suggesting that the walimah ursy is meant for more than one couple during a single walimah. The ban of 'Kembar Manten' in the framework of  Islamic legal anthropology is a customary practice within the community aimed at achieving well-being and security. Provided that the rules are designed to promote goodness and safety, it is imperative to preserve the values of local wisdom rules as a valuable cultural heritage of the nation. This article aims to enhance understanding of the customary law and local wisdom values in the Indonesian marital law.